CONCEPT, MODEL, AND IMPLEMENTATION OF STRATEGIC MANAGEMENT IN IMPROVING THE QUALITY OF ISLAMIC EDUCATION IN MAN 4 KEDIRI - Sulistio, Andi; Sulistyorini, Sulistyorini; Fitri, Agus Zaenul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Strategic management is the formulation of the strategic concept of an organization, or organizational sub-unit to achieve the desired goals. In madrasah, strategic management can be achieved through the cooperation of all elements. The purpose of writing this article is to understand the concept, model, and implementation of madrasah-based strategic management in improving the quality of education at MAN 4 Kediri. This research is a descriptive qualitative study to describe phenomena or events in depth and detail, focusing on understanding the context, experiences, and perceptions of research subjects. Data collection is done through observation, interviews and documentation studies which are then analyzed inductively to produce a holistic understanding of the phenomenon under study. The results showed that madrasah-based strategic management is a continuous process starting from strategic formulation, implementation, review and improvement. The model is in the form of management based on Balanced Scorecard (BSC), Information Technology, Total Quality (TQM), Educational Innovation, and Participatory management. In its implementation, the academic work program, student affairs, infrastructure and public relations are the basis for the preparation of the Madrasah Work Plan (RKM) which serves as a guideline for the implementation and development of the madrasah. This RKM produces quality education that is able to answer various challenges and problems.Quality improvement at MAN 4 Kediri can be seen by the number of students who continue their education to a higher level through the SMBT, SMBP and SPAN PTKIN channels.